Undue Burdens: How the Texas Abortion Ban (SB 8) Disproportionately Affects Low-Income Women - Ellen Mannion (Washington University Journal of Law and Policy, 2023)
A source of seemingly endless controversy, the legal status of abortion is of great importance, particularly for low-income women. Anti-abortion measures have consistently proven to disproportionately effect low-income women; one example of this is the Hyde Amendment passed in 1977, just three years after Roe v. Wade was decided. The Hyde Amendment barred the use of federal dollars for abortion services except in limited circumstances. except for when the life of the mother would be endangered by carrying the pregnancy to term. This Note highlights that the effects of the Hyde Amendment, combined with state restrictions on abortion services, results in significant consequences for low-income women seeking essential reproductive healthcare. Moreover, this Note focuses on how Texas Senate Bill 8 (“SB 8”) disproportionately affects low income women in all aspects of life. For instance, the costs of taking off work, traveling, and making the necessary arrangements to obtain an abortion are often affordable for middle- and upper-class women but the same cannot be said for a low-income woman choosing between securing needed reproductive healthcare and paying rent. The Author argues that because SB 8 is the most restrictive abortion law post Roe v. Wade, more low-income women will be forced to give birth to children for whom they may not be in a financial position to care, contributing further to the pernicious force of cyclical poverty. Furthermore, the Author proposes that Roe v. Wade be codified into federal law to break the cycle of poverty perpetuated by restrictive abortion bans such as SB 8. Disclaimer: This analysis was done in 2021 before the Supreme Court decided Dobbs v. Jackson Women’s Health in June of 2022 wherein Roe v. Wade was overturned. It is important to note that regardless of the Dobbs decision, this note focuses on the economic impact that restricted access to reproductive healthcare has on low-income women. In states where abortion is banned outright, that financial burden has since only grown.
Keywords: Roe; Abortion; Texas; SB 8; Low Income Women; Poverty